Hubungan Konsep Diri dan Penerimaan Diri dengan Tingkat Kecemasan Menjelang Bebas pada Warga Binaan Lapas - Erista Maharani; Amin Sihabuddin; Hartika Utami Fitri (Institut Agama Islam Negeri Curup, 2023)
The purpose of this study was to find out whether there is a significant relationship between self-concept and self-acceptance with the anxiety level before being relased in inmates. This research is a filed research with data collection techniques using a questionare. This research approach used a quantitative approach to the type of correlation or relationship research that aims to determine the relationship between teo or more variables. The research analysis used multiple correlations analysis. The sample used was 85 inmates before being relased. The sampling technique used is Simple Random Sampling. The results of this study partially show that there is a relationship between self-concept and self-acceptance with the level of anxiety before being released is low and vice versa. Simultaneously there is a relationship between self-concept and self-acceptance with the level of anxiety before being released with a contributions of 12% the rest is influenced by other external factors such as concerns about family views and the social environment.